A framework for identifying the linkability between Web servers for enhanced internet computing and E-commerce. Issue 1 (December 2017) - Artail, Hassan; El Halabi, Ammar; Hachem, Ali; Al-Akhrass, Louay
Abstract Existing Web session tracking techniques mainly work on huge web server log files, which limit their dynamicity and capability. We present a collaborative method for session tracking to identify direct and indirect web server interactions. The outcome could lead to building partnerships between organizations that do e-business, adapting links on websites to user click behavior, and deciding on the particular services offered by websites. We implemented a prototype that showed the usefulness and effectiveness of the system. We describe the significance and applications of our approach in e-commerce through information that describes traffic flows between websites.